Analysis of Muscle Activity Utilizing Bench Presses in the AnyBody Simulation Modelling System. (11th May 2016) - Ji, Zhongqiu; Wang, Huihui; Jiang, Guiping; Li, Lin
Abstract : Using the AnyBody human modeling system with identical weights and varying grip distance (40.0 cm, 50.0 cm, and 60.0 cm), the stress distribution for the pectoralis and the muscle of upper extremity during a bench press was simulated, and the surface myoelectricity (EMG) method was validated. Methods. The physical parameters driving the model of the human body were selected as weights of 35.0% (25.0 kg) and grip distances. Conclusion. The validation of AnyBody software was proved as a high validity by using EMG test of four muscles' activity compared to AnyBody software. During a bench press, the pectoralis major is the main muscle, the pectoralis major discharge increases with the height of barbell increases, and the pectoralis major discharge decreases as the short grip width increases. When the grip width equals the shoulder width, the value of pectoralis minor is lowest; when the grip width is smaller or larger than the shoulder width, the value is larger. As the short grip distance increases, the discharge of posterior deltoid muscle and triceps surface myoelectricity increases; thus, as the short grip distance increases, the deltoid muscle and triceps assist the pectoralis major during a bench press.